Recognising the real danger of SIM fraud. Issue 11 (November 2017) - Blaich, Andrew
Abstract : In today's digital society, we would struggle to get very far without our mobile devices. In fact, according to Emarketer, 2017 is the first year in which handheld devices have beaten the computer when it comes to online browsing. 1 The UK is a nation of on-the-go, always-on individuals. As our smartphones get smarter and more intuitive to our needs, cyber-criminals are shifting their attention away from desktops and PCs towards the potential of mobile devices.